Modern Political Theory - Hopper, Tucker [author]
Modern political theory is a branch of political science that focuses on the ideas and concepts of politics that have emerged since the Enlightenment in the 17th and 18th centuries. It is concerned with the study of the nature and purpose of political authority, the role of the state, and the relationship between the individual and the state.Overall, modern political theory seeks to provide a framework for understanding and analyzing the political systems, institutions, and practices that exist in modern societies, and to offer insights into how they can be improved and reformed. Modern political theory is a field within political science and philosophy that focuses on the development and analysis of political ideas and concepts from the Enlightenment era to the present day. It encompasses a wide range of influential thinkers, including but not limited to political philosophers like John Locke, Jean-Jacques Rousseau, Thomas Hobbes, Karl Marx, and contemporary political theorists. Modern political theory features a diverse array of influential thinkers, from classical figures like Thomas Hobbes and Karl Marx to contemporary scholars like Martha Nussbaum and Amartya Sen.. These individuals have contributed unique perspectives on topics like justice, equality, and the role of the state, enriching the discipline. Books on modern political theory often explore the key ideas, debates, and movements that have shaped political thought and practice in the modern world. They may cover topics such as democracy, liberalism, socialism, conservatism, feminism, nationalism, and global politics. These books can provide valuable insights into the evolution of political ideas and their impact on the organization of societies, governments, and international relations." -- Book cover